2016
DOI: 10.1088/0029-5515/56/12/124002
|View full text |Cite
|
Sign up to set email alerts
|

Plasma rotation from momentum transport by neutrals in tokamaks

Abstract: Neutral atoms can strongly influence the intrinsic rotation and radial electric field at the tokamak edge. Here, we present a framework to investigate these effects when the neutrals dominate the momentum transport. We explore the parameter space numerically, using highly flexible model geometries and a state of the art kinetic solver. We find that the most important parameters controlling the toroidal rotation and electric field are the major radius where the neutrals are localized and the plasma collisionali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…In Ref. [23] we found that the electric field increased with R n at high collisionality and decreased at low collisionality. The radius of the X-point decreases with increasing , so Fig.…”
Section: Low Order Shaping Parametersmentioning
confidence: 84%
See 3 more Smart Citations
“…In Ref. [23] we found that the electric field increased with R n at high collisionality and decreased at low collisionality. The radius of the X-point decreases with increasing , so Fig.…”
Section: Low Order Shaping Parametersmentioning
confidence: 84%
“…Comparison of analytical and numerical results for the dependence of (a) toroidal flow velocity and (b) radial electric field at the outboard midplane on poloidal location of the neutrals. Dashed lines show the banana regime analytic results, (23) and (22), and dotted lines the Pfirsch-Schlüter analytic results, (20) and (19). Solid lines show numerical scans, with colours from blue to red corresponding to low to high collisionalityν, as shown in the legend.…”
Section: Comparison To Analytical Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated here that charge-exchanging neutrals can carry a significant angular momentum flux in the tokamak edge. The formalism developed in [10,11] and first implemented numerically in [12] has been extended, to enable interpretive studies evaluating the momentum transport through neutrals for experimental profiles and equilibria. In this interpretive mode, the radial variation of the background profiles does not have to be neglected compared to the radial gradient of the neutral density.…”
Section: Discussionmentioning
confidence: 99%